Enhancing Coconut Productivity with Hybrid Varieties: A Community Service Initiative in Nusa Ela Village, Negeri Ureng - Fransina S Latumahina; Erik Pratama; Ainayyah Alfatiha Selay; Muhammad Saleh Irfan Hanubun (Indonesian Journal of Cultural and Community Development, 2023)
This study aimed to address challenges in coconut cultivation and enhance productivity in Nusa Ela Village, Negeri Ureng, through the implementation of a hybrid coconut cultivation method. Coconut (Cocos nucifera L.), a crucial tropical plant, demonstrates tremendous adaptability to various climatic and soil conditions. Despite Indonesia being the world's leading coconut producer, there exist significant issues affecting productivity, ranging from pests to socio-economic factors. To ameliorate these issues, our approach utilized superior varieties, specifically hybrid coconuts, known for their high adaptability and productivity. The hybrid coconut, a cross between dwarf and tall varieties, showed promising characteristics such as high oil content and the ability to produce approximately 140 fruits per tree annually, thus making it a potential solution for enhancing coconut productivity. The community service initiative involved conducting a hybrid coconut cultivation training program for the local farmers. The practical involvement of the community, coupled with continuous education and promotion of innovative and creative practices, manifested promising results. This approach could serve as a sustainable strategy to enhance coconut productivity and foster economic growth within the community, thereby contributing to the broader agro-industry field. The results of this study underscore the potential of hybrid coconut cultivation as a solution for the low productivity challenge in coconut farming, with implications for other tropical regions facing similar issues.Highlights: Hybrid coconuts boost productivity in tropical farming. Practical cultivation training empowers local communities. Innovative practices promote sustainable agro-industry. Keywords: Hybrid Coconut, Productivity, Tropical Agriculture, Community Service Initiative, Sustainable Farming